Accountability, Information and Communications Systems (AICS): Washington’s Approach to Accountability Reporting - Kathleen F. Duncan; H. Dennis Brown (Journal of Applied Communications, 2001)
This article describes AICS, a flexible, multi-purpose, Web-based Accountability, Information and Communications System developed by the College of Agriculture and Home Economics at Washington State University. Made up of more than 200 programs, the system collects, stores and retrieves information from faculty, regardless of appointment and specified staff. AICS’s single, standardized, reporting format supersedes previous annual faculty activity reports, which varied from department to department. The searchable database provides information for a wide variety of reporting needs, including accountability. Developed between 1998 and 1999, the system was implemented at the end of 1999. Ohio State University, Purdue University, Kansas State University and the University of Missouri have since purchased the software to adapt for their use. Kathleen Duncan has conducted workshops for each of these institutions. Ohio state University is currently using the system (http://www.oardc.ohio-state.edu/ursdevell/accountability/); the systems personnel at the other three universities expect to have the system in use by Fall 2001 (personal communication, April 26, 2001).